Leading Social Transformations: Creating Public Value and Advancing the Common Good. Issue 2 (3rd April 2021) - Bryson, John M.; Barberg, Bill; Crosby, Barbara C.; Patton, Michael Quinn
ABSTRACT: This essay explores what is involved in leading a social transformation to create public value and advance the common good. The contrast here is with strategic leadership of organizations, collaborations, and social movements. Leading a social transformation is much bigger . The required changes are multi-issue, multi-level, multi-organizational, and cross-sectoral, and can cross national frontiers. Deep and broad changes, often involving radical innovations, are needed. Deep and abiding changes in relationships – and power relationships – among people and groups are required. Leadership of organizations, collaborations, and social movements is still important for transformation, but not enough. Instead, advancing social transformation requires leadership that is deeply relational, visionary, political, adaptive, and comfortable with complexity.